Government Liability to Damages Due to Defective Provision of Health Services in Turkey - Yavuz Guloglu; Recep Yargıcı (Jurnal Cita Hukum, 2022)
Health service is one of the basic public services offered by the administration with a very comprehensive and wide staff, and due to the comprehensive nature of the service provided and the fact that the beneficiaries of the service constitute almost every segment of the society, many different appearances of defect that may constitute the compensation responsibility of the administration may arise. The study is mainly about the service defect and the compensation responsibility of the administration in the provision of health services within the scope of the responsibility of the administration based on service defect. In the study, the concept of the responsibility of the administration and the concepts of defect liability and strict liability, which are the types of responsibility of the administration, will be discussed first, and then the conditions of the responsibility of the administration will be examined. Then, the concept of service defect, the different forms of appearance of service defect, such as poor service, late service, non-operational service, and severe service defect will be examined. Finally, the service defects specific to health services, which constitute the main framework of the study, will be examined in the light of the decisions of the Council of State on this issue.